Tanhuo Formula Inhibits Astrocyte Activation and Apoptosis in Acute Ischemic Stroke - Nie, Yuting; Wen, Lulu; Li, Hui; Song, Juexian; Wang, Ningqun; Huang, Liyuan; Gao, Li; Qu, Miao (Frontiers in Pharmacology, 2022)
Tanhuo formula (THF), a traditional Chinese medicinal formula, has been demonstrated to be effective in the clinical treatment of acute ischemic stroke (AIS). However, its active ingredients, potential targets, and molecular mechanisms remain unknown. Based on the validation of active ingredient concentrations, our study attempted to elucidate the possible mechanisms of THF based on network pharmacological analysis and experimental validation. Components of THF were screened using network pharmacological analysis, and a compound-target network and protein–protein interaction (PPI) network were constructed. In total, 42 bioactive compounds and 159 THF targets related to AIS were identified. The PPI network identified AKT1, TNF, IL6, IL1B, and CASP3 as key targets. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis demonstrated that the inflammation and apoptotic pathways were enriched by multiple targets. The main components of THF were identified via high-performance liquid chromatography. Subsequently, a validation experiment was conducted, and the expressions of GFAP, C3, TNF-α, and IL-6 were detected via immunofluorescence staining, confirming the inflammatory response at 30 min and 3 days post injury. Immunohistochemical staining for caspase-3 and TUNEL was also performed to assess apoptosis at the same time points. These results indicate that THF can effectively decrease neural cell apoptosis through the caspase-3 pathway and restrain excessive abnormal activation of astrocytes and the release of TNF-α and IL-6, which might be accompanied by the recovery of motor function. Thus, THF may serve as a promising therapeutic strategy for AIS through multiple targets, components, and pathways.